Fetal ultrasound evaluation of skeletal dysplasia, apropos of a case of thanatophoric dysplasia - Lacunza Paredes, Rommel Omar (2016)
The case of a 30 weeks pregnant woman and her fetus affected by thanatophoric dysplasia (TD) type I, referred to our Maternal Fetal Medicine Unit, Hospital Nacional Daniel Alcides Carrión, Callao, Perú, due to suspicion of skeletal dysplasia is reported. On the ultrasound, characteristic signs of TD and markers related to high risk of lethality were found. Recommendations are suggested for ultrasound evaluation of suspected cases of skeletal dysplasia, as a differentiated approach to diagnosis.